Influence of lamb finishing system on animal performance and meat quality - Gallo, Sarita Bonagurio; Arrigoni, Mario De Beni [UNESP]; Lemos, Ana Lúcia Da Silva C.; Haguiwara, Márcia Mayumi Harada; Bezerra, Helena Viel Alves (Editora da Universidade Estadual de Maringá - EDUEM, 2019)
This study aimed to assess the influence of lamb finishing systems on zootechnical performance, as well as on carcass and meat quality. The experiment was conducted at the APTA’s experimental farm. Thirty-three lambs were used - both sexes, initial age of 90 ± 3 days, Texel with Santa Inês, each animal being one experimental unit, with 6 males and 5 females per treatment. Treatments consisted of: lambs finished on pasture, in semi-feedlot or in feedlot. The lambs were slaughtered with average live weight of 35 kg. Weight gain and carcass measures were taken by ultrasound. After slaughter, carcass conformation and yield, pH, temperature, color, water retention capacity and tenderness were measured. Animals finished on pasture had lower weight gain, were slaughtered at an older age, with lighter carcass weight, smaller loin area, lower shank compactness index, besides lighter shoulder and shank weights, compared to the other production systems (p < 0.05). There was no difference between the semi-feedlot and the feedlot systems for the assessed characteristics. In conclusion, production systems affect animal performance, as well as carcass and meat quality, especially when it comes to important production aspects, such as slaughter age and yield of premium cuts.
Keywords: carcass conformation; carcass cut; feedlot; meat quality; pasture; sheep